Trans-cinnamic acid-terminated polyarylester, preparation method and application

Through the end group crosslinking reaction of trans-cinnamic acid-capped polyarylene material, the problems of low strength and large shrinkage of existing optical resins were solved, and optical polyesters with high refractive index and good mechanical properties were prepared, which is suitable for High performance optical lens manufacturing.

CN119119435AActive Publication Date: 2024-12-13DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411259804.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing high-refractive index optical resins have problems with low intensity and large shrinkage when manufacturing optical lenses, and it is difficult to have both low shrinkage and high performance characteristics.

Method used

The polyarylene material with trans cinnamic acid end-capped is formed by using end-group crosslinking reaction to form optical polyesters with low shrinkage and high refractive index. Combined with heat-induced or photo-induced crosslinking technology, good optical and mechanical properties are prepared by combining heat-induced or photo-induced crosslinking technology. thermosetting material.

Benefits of technology

The refractive index at 589 nm is achieved to reach 1.62-1.66, and has a light transmittance of more than 88% and a tensile strength greater than 120 MPa, combining low shrinkage of thermoplastic materials and high performance of thermosetting materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119435A_ABST
    Figure CN119119435A_ABST
Patent Text Reader

Abstract

The invention discloses trans-cinnamic acid terminated polyarylester, a preparation method and application, the polyarylester has a structure shown in a formula I: # imgabs0 #, in the formula I, R is selected from at least one of phenolphthalein, bisphenol fluorene ether, methyl bisphenol fluorene, thymol phenolphthalein, bisphenol fluorene, isoindolinone and phenolphthalein; and n is in a range of 1 to 1000. Through a trans-cinnamic acid end-capping mode, an end group cross-linking reaction is carried out while a thermoplastic polymer is prepared, optical polyarylester with low shrinkage and high refractive index is further prepared, the refractive index (nd) of the material at 589nm can reach 1.62-1.66, the visible light transmittance is high and is greater than or equal to 88%, and the tensile strength is greater than 120MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a trans-cinnamic acid-terminated polyarylate, a preparation method and an application thereof, and belongs to the field of polymer materials. Background Art

[0002] With the rapid development of modern science and technology such as electronic science and the Internet, the application scope of optical lenses has expanded from the original film cameras, microscopes, telescopes, simple medical devices and other products to digital cameras, laptops, mobile phones, security surveillance cameras, vehicle-mounted visual systems, smart homes, aerial photography drones and many other optical imaging fields closely related to human life, and the application areas are becoming increasingly wide.

[0003] Resin lenses are popular due to their low manufacturing difficulty, high mass production capacity, low cost and light weight, and are also a hot topic in the current lens design field. The functions of high refractive index optical resins are mainly the following two points: 1. The refractive index of the lens is increased, which is convenient for aberration correction and can effectively improve the performance of the lens. 2. The high refractive index can reduce the height of the optical system and achieve a low total lens length (TTL), effectively realizing the miniaturization and lightweight of the lens.

[0004] As an optical resin, CN 201580023583.2 discloses a polycarbonate resin composition. Thermoplastic materials have a low shrinkage rate and can effectively realize injection molding, but their strength is low. Thermosetting materials have good stability, but the shrinkage rate is large. This patent is used to prepare a trans-cinnamic acid-terminated high-refractive index optical polyarylate, which can be further cross-linked by thermal initiation / photoinitiation to form a thermosetting material, which has both the low shrinkage rate of thermoplastic materials and the good optical and mechanical properties of thermosetting high-performance films. The refractive index is 1.62-1.66, the transmittance is ≥88%, and the tensile strength is greater than 120MPa. Summary of the invention

[0005] The present invention discloses a method for preparing a high-refractive-index optical polyarylate capped with trans-cinnamic acid and its application. By capping with trans-cinnamic acid, a low-shrinkage, high-refractive-index optical polyester is further prepared through a terminal cross-linking reaction while preparing a thermoplastic polymer.

[0006] According to the first aspect of the present application, a trans-cinnamic acid-terminated polyarylate is provided, wherein the polyarylate has a structure of formula I:

[0007]

[0008] In Formula I,

[0009] The R is selected from at least one of phenolphthalein, bisphenol fluorene ether, methyl bisphenol fluorene, thymolphthalein, bisphenol fluorene, isoindolinone, and phenolphthalein;

[0010] The n is 1-1000.

[0011] According to the second aspect of the present application, a method for preparing a trans-cinnamic acid-terminated polyarylate is provided.

[0012] At least the following steps are included:

[0013] Step I: dispersing diphenol monomer and catalyst in an organic solvent to form a mixture I;

[0014] Step II: dissolving the acyl chloride monomer in an organic solvent to form a mixture II;

[0015] Step III: adding the mixture II obtained in step II dropwise into the mixture in step I, and performing reaction I to obtain a terminal hydroxyl polymer;

[0016] Step IV: Add reverse cinnamic acid chloride to the polymer obtained in step III, and perform reaction II to obtain trans-cinnamic acid-terminated polyarylate.

[0017] Optionally, the diphenol monomer is selected from at least one of phenolphthalein, bisphenol fluorene ether, methyl bisphenol fluorene, thymolphthalein, bisphenol fluorene, isoindolinone, and phenolphthalein;

[0018] The catalyst is selected from at least one of triethylamine, nitrogen-methylimidazole, potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, and potassium bicarbonate;

[0019] The acyl chloride monomer is selected from at least one of terephthaloyl chloride, phthaloyl chloride and biphthaloyl chloride;

[0020] The organic solvent is selected from at least one of dichloromethane, chloroform, N,N-dimethylformamide, toluene, diphenyl ether, dimethylacetamide and xylene.

[0021] Optionally, in step III,

[0022] The reaction conditions are as follows:

[0023] The temperature of the reaction I is 10 to 220°C;

[0024] The reaction time of I is 4-XXh;

[0025] Wherein, when the temperature of reaction I is 200-220° C., reaction I is carried out under a nitrogen atmosphere.

[0026] Optionally, the molar concentration of the diphenol monomer in the mixed solution I is 0.075 to 0.15 mol / L;

[0027] The volume concentration of the catalyst in the mixed solution I is 0.008-4.15 g / L;

[0028] The molar concentration of the acyl chloride monomer in the mixed solution II is 0.075-0.14 mol / L;

[0029] The molar ratio of the acyl chloride monomer to the diphenol monomer is 1.02:1 to 0.97:1;

[0030] Optionally, in step IV,

[0031] The molar ratio of the trans-cinnamic acid to the acyl chloride monomer is 1:1000 to 1:100;

[0032] Optionally, the conditions of reaction II are as follows:

[0033] The reaction time of II is 0.5 to 48 hours;

[0034] The temperature of the reaction II is 10 to 220°C;

[0035] Wherein, when the temperature of reaction II is 200-220° C., the reaction I is carried out under a nitrogen atmosphere, and an absorbent is also added to the mixture.

[0036] Optionally, the agent is selected from at least one of sodium hydroxide, calcium hydroxide, sodium bicarbonate, potassium bicarbonate, potassium carbonate, and sodium carbonate;

[0037] The concentration of the absorbent is 0.1-2 mol / L;

[0038] Optionally, the absorbent and the acyl chloride monomer are in a ratio of 1:1 to 1:1000.

[0039] According to a third aspect of the present application, a method for preparing a trans-cinnamic acid-terminated polyarylate film is provided, comprising at least the following steps:

[0040] Step I: dissolving the trans-cinnamic acid-terminated polyarylate in an organic solvent containing an acyl chloride monomer, a diphenol monomer, and a catalyst, and adding a free radical initiator to obtain a solution A;

[0041] Step II: applying the solution A obtained in step I on a substrate to react and obtain a trans-cinnamic acid-terminated polyarylate film;

[0042] Optionally, in step I, the solid content of the organic solvent is 3 to 20%;

[0043] The free radical initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, benzoyl peroxide, and lauroyl peroxide.

[0044] Optionally, the molar ratio of the free radical initiator, the acyl chloride monomer and the diphenol monomer is 0.001:0.99-1.02:0.99-1.02.

[0045] Optionally, in step II, the substrate is selected from at least one of glass, quartz, indium tin oxide, and silicon wafer;

[0046] Optionally, the reaction conditions are as follows:

[0047] The reaction temperature is 230-240°C;

[0048] The reaction time is 0.5 to 48 hours.

[0049] Optionally, the trans-cinnamic acid-terminated polyarylate film has a refractive index of 1.62 to 1.66 at 589 nm;

[0050] Visible light transmittance 88-89%;

[0051] The tensile strength is 125~134Mpa.

[0052] The specific structure of the trans-cinnamic acid-terminated high-refractive-index optical polyarylate described in the present application is as follows:

[0053]

[0054] The structure of R can be phenolphthalein, bisphenol fluorene ether (BPEF), methyl bisphenol fluorene, thymolphthalein, bisphenol fluorene, isoindolinone, phenolphthalein containing cardo ring aromatic bisphenol.

[0055] The preparation process is as follows:

[0056] 1 The polymerization method can be a low temperature solution, a high temperature solution, or an interfacial polymerization method. Bisphenol is excessive, and trans-cinnamic acid chloride is added in the late stage of the polymerization reaction for end-capping.

[0057] 2 The bisphenol monomer in the polymer structure can be one or more of the R substitutions.

[0058] 3 The catalyst selected in the polymerization process can be one or more of triethylamine, nitrogen-methylimidazole, potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0059] 4 The polymerization product is a polymer with a terminal hydroxyl group, and a polymer with a terminal cinnamic acid group is prepared by further reacting with cinnamic acid chloride.

[0060] 5. Add a free radical initiator to form a cross-linked structure through free radical polymerization, wherein the catalyst for catalyzing the cross-linking reaction can be azobisisobutyronitrile, azobisisoheptylnitrile, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, benzoyl peroxide, and lauroyl peroxide. A solution casting method is used to prepare a high-performance, high-refractive-index optical film.

[0061] 6 In the preparation method, the molar ratio of the acyl chloride monomer to the diphenol monomer is 1.02:1, and the molar ratio of cinnamic acid to the acyl chloride monomer is 1:100.

[0062] 7. Reaction conditions of the preparation method, such as temperature, pressure, solid content, etc.

[0063] The beneficial effects of this application include:

[0064] The preparation method of the trans-cinnamic acid-terminated high-refractive-index optical polyarylate film of the present application is to prepare a thermoplastic polymer by means of trans-cinnamic acid-terminated method, and further prepare a low-shrinkage, high-refractive-index optical polyester by end-group cross-linking reaction. The refractive index (n d ) can reach 1.62-1.66, and has a high visible light transmittance ≥88%, and a tensile strength greater than 120MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is the H NMR spectrum of the trans-cinnamic acid-terminated polyarylate prepared in Example 1 of the present application;

[0066] Figure 2 This is the H NMR spectrum of the trans-cinnamic acid-terminated polyarylate prepared in Example 2 of the present application;

[0067] Figure 3 This is a gel permeation chromatogram of the trans-cinnamic acid-terminated polyarylate prepared in Example 4 of the present application;

[0068] Figure 4 This is the gel permeation chromatogram of the trans-cinnamic acid-terminated polyarylate prepared in Example 6 of the present application. DETAILED DESCRIPTION

[0069] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0070] Unless otherwise specified, the raw materials and catalysts in the examples and comparative examples of the present application were purchased through commercial channels.

[0071] The analysis methods in the examples and comparative examples of the present application are as follows:

[0072] The molecular structure of the obtained trans-cinnamic acid-terminated polyarylate was analyzed using a JNM-ECZL400S 400MHZ H-NMR spectrometer.

[0073] The molecular weight of the obtained trans-cinnamic acid-terminated polyarylate was tested using a Waters 2414 gel chromatography instrument;

[0074] The visible light transmittance of the film was tested using a Shimadzu UV-2600 ultraviolet-visible spectrophotometer.

[0075] The tensile strength of the film was tested using a mechanical universal testing machine.

[0076] The refractive index of the film was tested at 589 nm using an ATAGO DR-M2 Abbe refractometer.

[0077] This patent uses interfacial polymerization, low-temperature polymerization, high-temperature polymerization and other methods to prepare polyarylate-based polymers through polycondensation reactions. In the process, bisphenol forms end groups in excess, and cinnamic acid chloride is further added to form cinnamic acid end groups. On this basis, a catalyst is added to prepare a cross-linked structure through free radical polymerization to form the final product.

[0078] Example 1

[0079] Polyester was prepared by low-temperature solution polymerization using phenolphthalein and terephthaloyl chloride as raw materials. The preparation process is as follows: In a three-necked flask equipped with a mechanical stirrer, add phenolphthalein (3.34 g, 10.5 mmol) and triethylamine (3 mL), add to 70 mL of dichloromethane, and stir at 10°C for about 40 minutes. Slowly add 60 mL of dichloromethane solution containing terephthaloyl chloride (2.03 g, 10 mmol) to the above mixture, the viscosity gradually increases, and the addition is completed in about 30 minutes. Continue to react at 10°C. After 4 hours, add trans-cinnamic acid chloride (0.17 g, 1 mmol) and continue to react for 5 hours. The reaction product is precipitated in methanol and dried in vacuum at 60°C for 12 hours. The product nuclear magnetic hydrogen spectrum is shown Figure 1 , the chemical shift at 8.1ppm is the characteristic peak on the benzene ring of terephthaloyl chloride, and the chemical shift at 7.7ppm is the characteristic peak on the benzene ring of phenolphthalein lactone, indicating the successful preparation of polyester. 1g of the product was dissolved in 5mL of DMF solution, and azobisisobutyl cyanide (0.03g) was added. After removing bubbles, the solution was coated on a glass substrate and heated in vacuum at 230℃. After 24 hours, it was peeled off from the glass substrate to prepare a high-strength and high-refractive-index film. The visible light transmittance, tensile strength, and refractive index at 589nm of the film are shown in Table 1.

[0080] Example 2

[0081] The polyester precursor was prepared by low-temperature solution polymerization using bisphenol fluorene and terephthaloyl chloride as raw materials. The preparation process is as follows: In a three-necked flask equipped with a mechanical stirrer, add bisphenol fluorene (3.68g, 10.5mmol) and triethylamine (3mL), add to 60mL of dichloromethane, and stir at 10°C for about 40min. Slowly add 50mL of dichloromethane solution containing terephthaloyl chloride (2.03g, 10mmol) to the above mixture, the viscosity gradually increases, and the addition is completed in about 30min. Continue to react at 10°C. After 4h, add trans-cinnamic acid chloride (0.17g, 1mmol) and continue to react for 5h. The reaction product is precipitated in methanol and dried in vacuum at 80°C for 12h. The product NMR hydrogen spectrum is shown. Figure 2 The characteristic peaks of the benzene ring of terephthaloyl chloride at the chemical shift of 8.0ppm and the characteristic peaks of the benzene ring of bisphenol fluorene at the chemical shifts of 6.7ppm and 7.1ppm indicate the successful preparation of polyester. 8g of the product was dissolved in 40mL of toluene solution, and azobisisobutyl cyanide (0.03g) was added. After removing bubbles, the solution was coated on a quartz substrate and heated in vacuum at 200℃. After 24 hours, it was peeled off from the quartz substrate to prepare a high-strength and high-refractive-index film. The visible light transmittance, tensile strength, and refractive index of the film at 589nm are shown in Table 1.

[0082] Example 3

[0083] Polyester was prepared by low-temperature solution polymerization using isoindolinone and terephthaloyl chloride as raw materials. The preparation process is as follows: in a three-necked flask equipped with a mechanical stirrer, add isoindolinone (4.13g, 10.5mmol) and triethylamine (3mL), add to 70mL of chloroform, and stir at 10°C for about 40min. 60mL of chloroform solution containing terephthaloyl chloride (2.03g, 10mmol) was slowly added dropwise to the above mixture, the viscosity gradually increased, and the addition was completed in about 30min. At 10°C, the reaction continued. After 4h, trans-cinnamic acid chloride (0.085g, 0.5mmol) was added to the reaction and the reaction continued for 5h. The reaction product was precipitated in methanol and dried in vacuum at 60°C for 12h. 3 g of the product was dissolved in 15 mL of DMF solution, and benzoyl peroxide (0.03 g) was added. After removing bubbles, the solution was spread on a glass substrate and heated in vacuum at 230°C. After 24 hours, it was peeled off from the glass substrate to prepare a high-strength and high-refractive-index film. The visible light transmittance, tensile strength and refractive index of the film at 589 nm are shown in Table 1.

[0084] Example 4

[0085] Polyester is prepared by high-temperature solution polymerization using bisphenol fluorene ether and terephthaloyl chloride as raw materials and diphenyl ether as solvent. The preparation process is as follows: 70 mL of diphenyl ether solution containing terephthaloyl chloride (2.03 g, 10 mmol) is slowly added dropwise to the diphenyl ether solution containing bisphenol fluorene ether (3.46 g, 10.5 mmol). During the entire reaction process, a slow nitrogen flow is always maintained as a protective gas. Stir at 200°C for 4 hours, reflux reaction, 2000 mL of sodium hydroxide solution (concentration of 1 mol / L) as absorbent, after 4 hours of reaction, add trans-cinnamic acid chloride (0.085 g, 0.5 mmol) and continue the reaction for 5 hours. The reaction product is precipitated in methanol and dried in vacuum at 60°C for 12 hours. The product is shown in gel permeation chromatography. Figure 3 , number average molecular weight 3.5×10 4 g / mol, indicating the successful preparation of polyester. 0.05g of the product was dissolved in 5mL DMF solution, benzoyl peroxide (0.03g) was added, and after removing bubbles, the solution was spread on a glass substrate and heated in vacuum at 230°C. After 24 hours, it was peeled off from the glass substrate to prepare a high-strength and high-refractive-index film. The visible light transmittance, tensile strength, and refractive index of the film at 589nm are shown in Table 1.

[0086] Example 5

[0087] Polyester was prepared by high temperature solution polymerization using isoindolinone and terephthaloyl chloride as raw materials and diphenyl ether as solvent. The preparation process is as follows: 70 mL of diphenyl ether solution containing terephthaloyl chloride (2.03 g, 10 mmol) was slowly added dropwise to a diphenyl ether solution containing isoindolinone (4.13 g, 10.5 mmol). During the entire reaction process, a slow nitrogen flow was always maintained as a protective gas. Stir at 220 ° C for 4 hours, reflux reaction, 2000 mL of sodium hydroxide solution (concentration of 2 mol / L) as an absorbent, and after 4 hours of reaction, trans-cinnamic acid chloride (0.085 g, 0.5 mmol) was added to continue the reaction for 5 hours. The reaction product was precipitated in methanol and dried under vacuum at 60 ° C for 12 hours. 10 g of the product was dissolved in 50 mL of DMF solution, benzoyl peroxide (0.03 g) was added, and after removing bubbles, the solution was coated on a glass substrate and heated in vacuum at 240°C. After 24 hours, it was peeled off from the glass substrate to prepare a high-strength and high-refractive-index film. The visible light transmittance, tensile strength, and refractive index at 589 nm of the film are shown in Table 1.

[0088] Example 6

[0089] The polyester precursor was prepared by low-temperature solution polymerization using methyl bisphenol fluorene and terephthaloyl chloride as raw materials. The preparation process is as follows: In a three-necked flask equipped with a mechanical stirrer, add methyl bisphenol fluorene (3.73g, 10.5mmol) and nitrogen methyl imidazole (0.5g), add to 60mL of dichloromethane, and stir at 10°C for about 40min. Slowly add 50mL of dichloromethane solution containing terephthaloyl chloride (2.03g, 10mmol) to the above mixture, the viscosity gradually increases, and the addition is completed in about 30min. Continue to react at 10°C. After 4h, add trans-cinnamic acid chloride (0.34g, 2mmol) and continue to react for 5h. The reaction product is precipitated in methanol. After precipitation, it is dried in vacuum at 80°C for 12h. The product is shown in gel permeation chromatography. Figure 4 , number average molecular weight 3.8×10 4 g / mol, indicating the successful preparation of polyester. 6g of the product was dissolved in 30mL toluene solution, benzoyl peroxide (0.03g) was added, and after removing bubbles, the solution was coated on a quartz substrate and heated in vacuum at 200℃. After 24 hours, it was peeled off from the quartz substrate to prepare a high-strength and high-refractive-index film. The visible light transmittance, tensile strength, and refractive index of the film at 589nm are shown in Table 1.

[0090] Comparative Example 1

[0091] Polyester was prepared by low-temperature solution polymerization using phenolphthalein and terephthaloyl chloride as raw materials. The preparation process is as follows: Phenolphthalein (3.34 g, 10.5 mmol) and triethylamine (3 mL) were added to 70 mL of dichloromethane in a three-necked flask equipped with a mechanical stirrer, and stirred at 10°C for about 40 min. 60 mL of dichloromethane solution containing terephthaloyl chloride (1.99 g, 10 mmol) was slowly added dropwise to the above mixture, and the viscosity gradually increased. The addition was completed in about 30 min, and the reaction was continued at 10°C for 5 h. The reaction product was precipitated in methanol, and after precipitation, it was vacuum dried at 60°C for 12 h. The product was dissolved in a DMAc solution with a solid content of 20%, and after removing bubbles, the solution was coated on a glass substrate, vacuum heated at 230°C, and after 24 hours, it was peeled off from the glass substrate to prepare a high-strength and high-refractive-index film. The visible light transmittance, tensile strength, and refractive index of the film at 589 nm are shown in Table 1.

[0092] Table 1

[0093]

[0094] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A trans-cinnamic acid-terminated polyarylate, characterized in that: The polyarylate has the structure of Formula I: In Formula I, the R is at least one selected from phenolphthalein, bisphenol fluorene ether, methyl bisphenol fluorene, thymolphthalein, bisphenol fluorene, isoindolinone, and phenolphthalein; The n is 1-1000.

2. The method for preparing the trans-cinnamic acid-terminated polyarylate according to claim 1, characterized in that: The method comprises at least the following steps: Step I: dispersing diphenol monomer and catalyst in an organic solvent to form a mixture I; Step II: dissolving the acyl chloride monomer in an organic solvent to form a mixture II; Step III: adding the mixture II obtained in step II dropwise into the mixture in step I, and performing reaction I to obtain a terminal hydroxyl polymer; Step IV: Add reverse cinnamic acid chloride to the polymer obtained in step III, and perform reaction II to obtain trans-cinnamic acid-terminated polyarylate.

3. The method for preparing trans-cinnamic acid-terminated polyarylate according to claim 2, characterized in that: The diphenol monomer is at least one selected from phenolphthalein, bisphenol fluorene ether, methyl bisphenol fluorene, thymolphthalein, bisphenol fluorene, isoindolinone, and phenolphthalein; The catalyst is selected from at least one of triethylamine, nitrogen-methylimidazole, potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, and potassium bicarbonate; The acyl chloride monomer is selected from at least one of terephthaloyl chloride, phthaloyl chloride and biphthaloyl chloride; The organic solvent is selected from at least one of dichloromethane, chloroform, N,N-dimethylformamide, toluene, diphenyl ether, dimethylacetamide and xylene.

4. The method for preparing trans-cinnamic acid-terminated polyarylate according to claim 2, characterized in that: In step III, The conditions of the reaction I are as follows: The temperature of the reaction I is 10 to 220°C; The reaction time is 0.5 to 48 hours; Wherein, when the temperature of reaction I is 200-220° C., reaction I is carried out under a nitrogen atmosphere.

5. The method for preparing trans-cinnamic acid-terminated polyarylate according to claim 2, characterized in that: The molar concentration of the diphenol monomer in the mixed solution I is 0.075-0.15 mol / L; The volume concentration of the catalyst in the mixed solution I is 0.008-4.15 g / L; The molar concentration of the acyl chloride monomer in the mixed solution II is 0.075-0.14 mol / L; The molar ratio of the acyl chloride monomer to the diphenol monomer is 1.02:1 to 0.97:

1.

6. The method for preparing trans-cinnamic acid-terminated polyarylate according to claim 2, characterized in that: In step IV, The molar ratio of the trans-cinnamic acid to the acyl chloride monomer is 1:10000 to 1:100; Preferably, the conditions of reaction II are as follows: The reaction time of II is 0.5 to 48 hours; The temperature of the reaction II is 10 to 220°C; Wherein, when the temperature of reaction II is 200-220°C, the reaction I is carried out under a nitrogen atmosphere, and an absorbent is also added to the mixture; Preferably, the absorbent is selected from at least one of sodium hydroxide, calcium hydroxide, sodium bicarbonate, potassium bicarbonate, potassium carbonate, and sodium carbonate; The concentration of the absorbent is 0.1-2 mol / L; Preferably, the absorbent and the acyl chloride monomer are in a ratio of 1:1 to 1:1000.

7. A method for preparing a trans-cinnamic acid-terminated polyarylate film, characterized in that: At least the following steps are included: Step I: dissolving the trans-cinnamic acid-terminated polyarylate in an organic solvent containing an acyl chloride monomer, a diphenol monomer, and a catalyst, and adding a free radical initiator to obtain a solution A; Step II: applying the solution A obtained in step I on a substrate to react and obtain a trans-cinnamic acid-terminated polyarylate film; The trans-cinnamic acid-terminated polyarylate is prepared by the preparation method described in any one of claims 2 to 6.

8. The preparation method according to claim 7, characterized in that: In step I, the solid content of the organic solvent is 3 to 20%; The free radical initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, benzoyl peroxide, and lauroyl peroxide; Preferably, the molar ratio of the free radical initiator, the acyl chloride monomer and the diphenol monomer is 0.001:0.99-1.02:0.99-1.

02.

9. The preparation method according to claim 7, characterized in that: In step II, the substrate is selected from at least one of glass, quartz, indium tin oxide, and silicon wafer; Preferably, the reaction conditions are as follows: The reaction temperature is 230-240°C; The reaction time is 0.5 to 48 hours.

10. The preparation method according to claim 7, characterized in that: The trans-cinnamic acid-terminated polyarylate film has a refractive index of 1.62 to 1.66 at 589 nm; Visible light transmittance 88-89%; The tensile strength is 125~134Mpa.

Citation Information

Patent Citations

  • Azobenzene and cinnamic acid ester group-containing side-chain-type liquid crystal polymer membrane material and synthetic method therefor

    CN103374125A

  • Preparation of polyarylates

    EP0005858A1

  • Phenolphthalein polyarylate polymers and alloy compositions thereof

    EP0279091A1

  • Optical resin and its production

    JP1987000510A

  • Polyester polymer and its production

    JP2000319366A